2021
DOI: 10.15541/jim20200529
|View full text |Cite
|
Sign up to set email alerts
|

Molten Salt Synthesis of Nanolaminated Sc2SnC MAX Phase

Abstract: The MAX phases are a family of of ternary layered material with both metal and ceramic properties, and it is also precursor materials for synthesis of two-dimensional MXenes. The theory predicted that there are more than 600 stable ternary layered MAX phases. At present, there are more than 80 kinds of ternary MAX phases synthesized through experiments, and few reports on MAX phases where M is a rare earth element. In this study, a new MAX phase Sc2SnC with rare earth element Sc at the M sites was synthesized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 40 publications
1
6
0
Order By: Relevance
“…The XRD pattern of the product, obtained through experimental measurements and Rietveld refinement, is depicted in Figure 1a, which found that the X-ray diffraction (XRD) of the product shares similarities with the previously reported Sc 2 SnC MAX phase. 43 This indicates the synthesis of a 211-type Sc 2 GaC MAX phase. Notably, significant changes in the intensity of the (002), (004), and (006) crystal planes were observed, suggesting a preferential growth on the 00l crystal planes.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…The XRD pattern of the product, obtained through experimental measurements and Rietveld refinement, is depicted in Figure 1a, which found that the X-ray diffraction (XRD) of the product shares similarities with the previously reported Sc 2 SnC MAX phase. 43 This indicates the synthesis of a 211-type Sc 2 GaC MAX phase. Notably, significant changes in the intensity of the (002), (004), and (006) crystal planes were observed, suggesting a preferential growth on the 00l crystal planes.…”
Section: Resultsmentioning
confidence: 93%
“…In 2021, a Sc 2 SnC MAX phase was synthesized, representing the initial ternary Sc-based MAX phase. 43,44 This achievement has provided a path for further research and synthesis of ternary Sc-based MAX phases. Furthermore, the physical properties of MAX phases are significantly influenced by the presence of abundant A-site elements (e.g., Al, Si, Ga, In, and Sn).…”
mentioning
confidence: 93%
“…Zhao et al determined the interesting electrochemical performance of Nb 2 SnC in Li-ion electrolytes, which has sparked great interest in the scientific community for Sn-containing MAX phases. Following this report, two Sn-based MAX phases were synthesized, and lithiation in the Sn-based 211 MAX phases was performed theoretically. Moreover, a set of theoretical studies have reported different physical properties of Sn-based MAX phases. The structural, electronic, mechanical and lattice dynamical properties of Sc 2 SnC, including defect processes, in comparison to those of existing M 2 SnC MAX phases are reported in a recent study .…”
Section: Introductionmentioning
confidence: 99%
“…In an article published in mid-2019, this number was reported as 82 on the MAX phase list . After publishing this list, the newly synthesized MAX phases are Nb 2 SB, Zr 2 SB, Hf 2 SB, Sc 2 SnC, Ta 2 FeC, Ti 2 FeN, Nb 2 FeC, Zr 2 SeC, Hf 2 SeC, Hf 2 SeB, Zr 2 SeB, Hf 2 TeB, and Sc 2 PbC. It is noteworthy that common elements have been replaced with unusual elements at any one or more of the M, A, and X-sites of these new MAX phases. Hf 2 TeB is the most recent compound synthesized in the 211 MAX family within the Hf–A–B system .…”
Section: Introductionmentioning
confidence: 99%